2019
DOI: 10.1097/bsd.0000000000000899
|View full text |Cite
|
Sign up to set email alerts
|

Is Modified K-line a Powerful Tool of Surgical Decision Making for Patients With Cervical Spondylotic Myelopathy?

Abstract: Study Design: Prospective observational single-center study. Objective: To evaluate anterior decompression and fusion (ADF) or posterior surgery (PS) for patients with cervical spondylotic myelopathy (CSM) using the modified K-line (mK-line) and to compare clinical and radiologic outcomes between these 2 techniques. Summary of Background Data: The authors have previously reported that insufficient posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…If the distance between the anterior compression and the k-line is lower than 4 mm, posterior surgery will not allow for sufficient cord shift and an appropriate decompression, and an anterior surgery is recommended. 50 …”
Section: Surgical Decision-making In Dcmmentioning
confidence: 99%
“…If the distance between the anterior compression and the k-line is lower than 4 mm, posterior surgery will not allow for sufficient cord shift and an appropriate decompression, and an anterior surgery is recommended. 50 …”
Section: Surgical Decision-making In Dcmmentioning
confidence: 99%
“…31 Anterior Cervical Discectomy and Fusion ACDF is the most common anterior procedure performed in the treatment of CSM. 2,26,[31][32][33] Cervical sagittal parameters are closely related with clinical outcomes after multilevel ACDF. A retrospective review by Fan et al 11 discovered that longer symptom duration, lower preoperative JOA score, smaller change in Cobb angle, and a larger change in SVA were identified as risk factors of poor clinical outcomes.…”
Section: Preferred Treatment Optionsmentioning
confidence: 99%
“…Shamji et al 62 expanded on this and reported that patients with preoperative cervical lordosis exhibited significantly improved postoperative outcomes compared with patients with preoperative cervical kyphosis. In an effort to enhance surgical decision-making for CSM patients, Hirai et al 63 proposed the use of the modified K-line (mK-line) and minimum interval of the spinal cord (INT) to aid in surgical decision-making. Using a sagittal T1-weighted image, the mK-line was drawn from the midpoint of the spinal cord at C2-C7 and INT defined as the minimum distance from the mK-line to the anterior most compression factor.…”
Section: Posterior-based Approachesmentioning
confidence: 99%